2021
DOI: 10.3390/beverages7010011
|View full text |Cite
|
Sign up to set email alerts
|

Short Wave Ultraviolet Light (UV-C) Effectiveness in the Inactivation of Bacterial Spores Inoculated in Turbid Suspensions and in Cloudy Apple Juice

Abstract: Liquid foods might present interferences in their optical properties that can reduce the effectiveness of short-wave ultraviolet radiation (UV-C) treatments used for sterilization purposes. The effect of turbidity as UV-C interference factor against the inactivation of bacterial spores was analysed by using phosphate-buffered saline solutions (PBS) of different turbidity values (2000, 2500, and 3000 NTU) which were adjusted with the addition of apple fibre. These suspensions were inoculated with spores of Baci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For example, Wilson et al (1992) observed that E. coli O157:H7 ATCC 43894 had an initial shoulder with slow inactivation (initial reduction), followed by first-order kinetics up to 5-log 10 , with D 10 in the log-linear region of about 1.2 mJ·cm -2 . It is also worth mentioning that most microbial challenge studies are carried out at 254 nm (Vashisht et al, 2022; Sauceda-Gálvez et al, 2021; Bhullar et al, 2019; Usaga et al, 2017; Chandra et al, 2017; Gunter-Ward et al, 2017; Torkamani, 2011), limited data is available at 263 nm wavelength. Akgün and Ünlütürk, 2017 studied the effects of Ultraviolet light-emitting diodes (UV-LEDs) on the inactivation of E. coli K12 (ATCC 25253), an indicator organism of E. coli O157:H7 in cloudy apple juice.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wilson et al (1992) observed that E. coli O157:H7 ATCC 43894 had an initial shoulder with slow inactivation (initial reduction), followed by first-order kinetics up to 5-log 10 , with D 10 in the log-linear region of about 1.2 mJ·cm -2 . It is also worth mentioning that most microbial challenge studies are carried out at 254 nm (Vashisht et al, 2022; Sauceda-Gálvez et al, 2021; Bhullar et al, 2019; Usaga et al, 2017; Chandra et al, 2017; Gunter-Ward et al, 2017; Torkamani, 2011), limited data is available at 263 nm wavelength. Akgün and Ünlütürk, 2017 studied the effects of Ultraviolet light-emitting diodes (UV-LEDs) on the inactivation of E. coli K12 (ATCC 25253), an indicator organism of E. coli O157:H7 in cloudy apple juice.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Wilson et al (1992) observed that E. coli O157:H7 ATCC 43894 had an initial shoulder with slow inactivation (initial reduction), followed by first‐order kinetics up to 5‐log 10 , with D 10 in the log‐linear region of about 1.2 mJ/cm 2 . It is also worth mentioning that most microbial challenge studies are carried out at 254 nm (Bhullar, Patras, Kilonzo‐Nthenge, Pokharel, & Sasges, 2019; Chandra et al, 2017; Gunter‐Ward et al, 2017; Sauceda‐Gálvez, Martinez‐Garcia, Hernández‐Herrero, Gervilla, & Roig‐Sagués, 2021; Torkamani, 2011; Usaga, Manns, Moraru, Worobo, & Padilla‐Zakour, 2017; Vashisht et al, 2022), limited data is available at 263 nm wavelength. Akgün & Ünlütürk, 2017 studied the effects of ultraviolet light‐emitting diodes (UV‐LEDs) on the inactivation of E. coli K12 (ATCC 25253), an indicator organism of E. coli O157:H7 in cloudy AJ.…”
Section: Resultsmentioning
confidence: 99%
“…A great example was demonstrated in McSharry et al, (2022), where Listeria monocytogenes T1093, illustrated an initial reduction, then, subsequently first-order kinetics up to 6-log 10 , with D 10 in the log-linear region of about 1.8 mJ·cm -2 (McSharry et al, 2022). Presently, many microbial challenge studies in liquid foods and beverages have been carried out at 254nm (Vashisht, et al, 2022; Sauceda-Gálvez, et al, 2021; Bhullar, et al, 2019; Usaga, et al, 2017; Chandra, et al, 2017; Gunter-Ward, et al, 2017; Torkamani & Niakousari, 2011), however, there is very limited data that is available at the 279 nm wavelength in UV-C microbial challenge studies. We hypothesize that D 10 value at 254 and 279nm will be very comparable but the optical properties of the suspensions will be significantly different.…”
Section: Resultsmentioning
confidence: 99%